2012
DOI: 10.1080/14635240.2012.661952
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy and colorectal cancer knowledge and awareness among African-American males

Abstract: Colorectal cancer (CRC) is the second leading cause of cancer deaths in the USA; however, the American Cancer Society estimates that as many as half of these deaths could be eliminated with annual CRC screenings. African-American males are less likely to participate in CRC screening when compared to white males. Despite the evidence that adult and health literacies are important variables in understanding racial/ethnic differences in health status and health-related knowledge of diseases, few studies have exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This result supports previous studies found that African Americans with low health literacy also had low knowledge concerning CRC and CRC screening. 35,36 Health literacy may be especially important to consider in the context of CRC screening because 1) many CRC screening interventions incorporate pamphlets or other materials that must be read and 2) written instructions accompany the screening test procedures themselves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result supports previous studies found that African Americans with low health literacy also had low knowledge concerning CRC and CRC screening. 35,36 Health literacy may be especially important to consider in the context of CRC screening because 1) many CRC screening interventions incorporate pamphlets or other materials that must be read and 2) written instructions accompany the screening test procedures themselves.…”
Section: Discussionmentioning
confidence: 99%
“…33 Studies have found that low health literacy is associated with low CRC screening knowledge. 34-36 However, another study found that perceived high-quality HCP communication mediated the association between low health literacy and low CRC screening knowledge. 34 In order to improve CRC screening utilization, it is important to understand the relationships among health literacy, cultural factors such as HCP trust, CRC knowledge, and CRC screening adherence.…”
Section: Introductionmentioning
confidence: 98%
“…Health literacy, defined as the ability to access, understand, and use health-related information to make informed decisions and manage health (Peerson & Saunders, 2009), is a key consideration for designing men's health promotion and disease-specific psychoeducation programs (Agho et al, 2012;Allen, Kennedy, Wilson-Glover, & Gilligan, 2007;Geller et al, 2006). Health literacy is directly linked to health outcomes (American Medical Association, 1999) and to behavioral predictors of health, such as physical activity (Al Sayah, Johnson, & Vallance, 2016;Geboers, de Winter, Luten, Jansen, & Reijneveld, 2014).…”
Section: Prostate Cancermentioning
confidence: 99%
“…After removing duplicates, 19,095 studies underwent title and abstract screening, and then 1541 full‐text studies were assessed for eligibility. In total, 699 studies were included, of which 144 were unique intervention studies included in the current analysis (representing 150 articles) 23–172 …”
Section: Resultsmentioning
confidence: 99%